Clinical characteristics and prognoses in pediatric neuroblastoma with bone or liver metastasis: data from the SEER 2010-2019 - Xudong Zhao; Zhuofan Xu; Xiaochuan Feng (BMC, 2024)
Abstract Background To investigate clinical characteristics, prognoses, and impacts of treatments on prognoses of neuroblastoma patients with bone or liver metastasis. Methods This retrospective cohort study extracted data from the Surveillance, Epidemiology, and End Results (SEER) database 2010-2019. The outcomes were 3-year cancer-specific survival (CSS) and 5-year CSS. Multivariable COX risk proportional models were established to assess the association between metastasis types and CSS. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated. Results Totally 425 patients with metastatic neuroblastoma were eligible for 3-year CSS analysis and 320 for 5-year CSS analysis. For 3-year follow-up, 62 (14.59%) patients had liver metastasis alone, 289 (0.68%) had bone metastasis alone, and 74 (17.41%) had both liver and bone metastasis. For 5-year follow-up, 44 (13.75%) patients had liver metastasis alone, 223 (69.69%) had bone metastasis alone, and 53 (16.56%) had both liver and bone metastasis. Significant differences were observed in age, tumor size, surgery for the primary site, chemotherapy, radiation, brain metastasis, lung metastasis, and vital status between patients with liver metastasis alone, bone metastasis alone, and both liver and bone metastasis (all P < 0.05). Compared with patients with liver metastasis alone, patients with bone metastasis alone (HR = 2.30, 95%CI: 1.10-4.82, P = 0.028) or both (HR = 2.35, 95%CI: 1.06-5.20, P = 0.035) had significantly poorer 3-year CSS; patients with bone metastasis alone (HR = 2.32, 95%CI: 1.14-4.70, P = 0.020) or both liver and bone metastasis (HR = 2.33, 95%CI: 1.07-5.07, P = 0.032) exhibited significantly worse 5-year CSS than those with liver metastasis alone. In patients with bone metastasis, those with chemotherapy had significantly better 3-year CSS than those without (HR = 0.24, 95%CI: 0.07-0.75, P = 0.014). Among patients with liver metastasis, receiving radiation was associated with significantly worse 3-year CSS (HR = 2.00, 95%CI: 1.05-3.81, P = 0.035). Conclusion Compared with patients with liver metastasis alone, those with bone metastasis alone or both had poorer 3- and 5-year CSS. For patients with bone metastasis, undergoing chemotherapy was associated with better 3-year CSS. For patients with liver metastasis, receiving radiation was associated with worse 3-year CSS.